Protocols for translocation processes of flexible polymers through a pore using LAMMPS - Vrinda Garg; Rejoy Mathew; Arindam Chatterjee; Surya K. Ghosh (STAR Protocols)
Summary: Large-scale Atomic/Molecular Massively Parallel Simulator (LAMMPS) is an open-source, powerful simulator with a customizable platform for extensive Langevin dynamics simulations. Here, we present a protocol for using LAMMPS to develop coarse-grained models of polymeric systems with macromolecular crowding, an integral part of any soft matter or biophysical system. We describe steps for installing software, using LAMMPS basic commands and code, and translocating polymers. This protocol has potential applications in developing mathematical models for DNA sequencing, controlled drug delivery, and cellular transport processes.For complete details on the use and execution of this protocol, please refer to Garg et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.